2018
DOI: 10.3390/s18051321
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of Fatigue Crack Growth in Gas Turbine Engine Blades Using Acoustic Emission

Abstract: Fatigue failure is the main type of failure that occurs in gas turbine engine blades and an online monitoring method for detecting fatigue cracks in blades is urgently needed. Therefore, in this present study, we propose the use of acoustic emission (AE) monitoring for the online identification of the blade status. Experiments on fatigue crack propagation based on the AE monitoring of gas turbine engine blades and TC11 titanium alloy plates were conducted. The relationship between the cumulative AE hits and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(20 citation statements)
references
References 35 publications
1
19
0
Order By: Relevance
“…In aircraft components, the AE technology was used to detect fatigue cracks under a load [ 28 , 29 , 30 ]. In a storage tank, AE testing was used to monitor the storage tank health and to detect and locate corrosion and leakage in the bottom plate of storage tank [ 31 , 32 ].…”
Section: Introductionmentioning
confidence: 99%
“…In aircraft components, the AE technology was used to detect fatigue cracks under a load [ 28 , 29 , 30 ]. In a storage tank, AE testing was used to monitor the storage tank health and to detect and locate corrosion and leakage in the bottom plate of storage tank [ 31 , 32 ].…”
Section: Introductionmentioning
confidence: 99%
“…The acoustic emission (AE) technique is a promising non-destructive surveillance technology for materials study and in situ supervision of structures [ 3 ]. The acoustic emission detection technique has been widely used in damage detection of metallic materials [ 4 , 5 , 6 ], composite materials [ 7 , 8 , 9 ], and rock materials [ 10 , 11 , 12 , 13 ]. Ennaceur et al [ 6 ] studied the damage and cracking of two metallic materials, 304L and P265GH steel, the using acoustic emission technique, which found that acoustic emission parameters such as count and amplitude can be used to characterize different crack propagation mechanisms.…”
Section: Introductionmentioning
confidence: 99%
“…Accurately identifying the location of microscopic fractures and damage is the scientific basis for researching the failure mechanism of materials, predicting rock bursts, and safely operating large industrial equipment [10][11][12][13][14][15][16][17]. Therefore, it is highly worthwhile to develop a high-precision AE source location method [18][19][20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%